Hypokalemic Paralysis Secondary to Immune Checkpoint Inhibitor Therapy - Pragathi Balakrishna; Augusto Villegas (Case Reports in Oncological Medicine)
Introduction of immune checkpoint inhibitors (ICIs) has led to significant improvements in the treatment of multiple malignancies. Anti-programmed cell death protein 1 (PD-1) and anti-cytotoxic T-lymphocyte antigen 4 (CTLA-4) are two essential ICIs that have been FDA approved since 2011. As the use of immunotherapy in melanoma and other malignancies increases, the potential of adverse events also increases. Overall, anti-PD-1 agents are well tolerated. In rare instances, colitis, endocrinopathies, skin, and renal toxicities have been observed. A 58-year-old male with a history of stage 4 cutaneous melanoma presented with quadriplegia while on nivolumab. Routine blood test revealed low potassium, low bicarbonate, and high serum creatinine. Admission diagnosis included hypokalemia, acute kidney injury, and renal tubal acidosis. The offending drug was discontinued, and the patient was started on high-dose corticosteroids. On discharge, paralysis was resolved. Renal function and potassium were normalized. Nivolumab was discontinued, and he was started on pembrolizumab. Literature suggests that, although rare, patients receiving ICE may develop immune-mediated nephritis and renal dysfunction. The mainstay of immune-related adverse event (irAE) management is immune suppression. Hence, given the increasing frequency of immunotherapy use, awareness should be raised in regard to irAEs and their appropriate management.